2020
DOI: 10.9770/jesi.2020.8.2(35)
|View full text |Cite
|
Sign up to set email alerts
|

Investment incentives as instrument of motivation of firms and economic stabilization

Abstract: Investment incentives are mostly presented as an efficient tool of economic policy to eliminate negative impacts of economic cycle and also as the tools of motivation of firms to generation of investment. The aim of the paper is to verify the relationship between investment incentives and business cycle in the Czech Republic. There is used the data of CzechInvest, Czech Statistical Office and Organisation for Economic Cooperation and Development. To verify the link between the investment incentives and the bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Different driving factors can explain dynamics and market selection processes of enterprises Xavier 2004, 2007) and strategies of their survival (Bojnec and Knific 2021), economic and financial performances of enterprises, such as corporate governance (Bhagat and Bolton 2008;Koji et al 2020), state aid, the effectiveness of investment incentives (Cedidlová 2013;Fabuš and Csabay 2018;Musil and Hedija 2020), a macro-economic enabling environment with greater economic freedom, investment cost subsidy, and tax reduction incentives for investment that enhance the increases in inflow of FDI (Sambharya and Rasheed 2015;Munongo et al 2017;Tian 2018), and the availability of working capital and its management (Akgun and Karatas 2021;Anton and Nucu 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Different driving factors can explain dynamics and market selection processes of enterprises Xavier 2004, 2007) and strategies of their survival (Bojnec and Knific 2021), economic and financial performances of enterprises, such as corporate governance (Bhagat and Bolton 2008;Koji et al 2020), state aid, the effectiveness of investment incentives (Cedidlová 2013;Fabuš and Csabay 2018;Musil and Hedija 2020), a macro-economic enabling environment with greater economic freedom, investment cost subsidy, and tax reduction incentives for investment that enhance the increases in inflow of FDI (Sambharya and Rasheed 2015;Munongo et al 2017;Tian 2018), and the availability of working capital and its management (Akgun and Karatas 2021;Anton and Nucu 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The estimation results obtained by Yanikkaya and Karaboga (2017) showed that investment incentives had a negative or, at best, no positive effect on the selected macroeconomic variables. Although Musil and Hedija (2020)-only on a basis of a correlation analysisdemonstrated a statistically significant positive relationship between investment incentives and GDP growth, they also pointed to a non-statistically significant relationship between investment incentives and the output gap. Thus, they generally concluded that the investment promotion policy did not react flexibly to the current needs of the Czech economy.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Hlaváček and Janáček (2019) researched various impacts of foreign investment and investment incentives on socio-economic development in Czechia, including that FDI and investment incentives are considered positive for a regionʼs economic growth. Musil and Hedija (2020) analysed the relationship between investment incentives and the economic cycle and determined that investment incentives are pro-cyclic. Similarly, Dinga (2011) examined the impact of investment incentives on the location of direct foreign investment in Czechia in 2001 -2007.…”
Section: Investment Incentives and Fdi In The Czechmentioning
confidence: 99%